Associations between COVID-19 infection and sex steroid hormones - Cai, Zixin; Zhong, Jiaxin; Jiang, Yingling; Zhang, Jingjing (Frontiers in Endocrinology, 2022)
Aims Coronavirus disease 2019 (COVID-19) is caused by infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), and within a few months of the first outbreak, it was declared a global pandemic by the WHO. The lethal virus SARS-CoV-2 is transmitted through respiratory droplets and enters host cells through angiotensin-converting enzyme 2 (ACE-2) receptors. ACE-2 receptors are highly expressed in many tissues, including testes. Therefore, the objective of this study was to summarize the available literature regarding the correlation between sex hormone levels and COVID-19. Methods The PubMed, Web of Science, Embase, and Cochrane Library databases were reviewed systematically through August 2022 for studies comparing sex hormone levels between different patient groups: COVID-19 versus no COVID-19, more severe versus less severe COVID-19, and non-survivors versus survivors. Various types of clinical research reporting sex hormone levels, including free testosterone (FT), luteinizing hormone (LH), follicle-stimulating hormone (FSH), 17β-oestradiol (E2), the oestradiol-to-testosterone ratio (E2/T), prolactin (PRL), and sex hormone-binding globulin (SHBG), were included. Random- or fixed-effects models were used to calculate weighted mean differences (WMDs) and 95% confidence intervals (CIs). Heterogeneity among the studies was assessed by the I2 index, and data analyses were performed using meta-analysis with Stata version 12.0. Results Twenty-two articles that included 3369 patients were ultimately included in the meta-analysis. According to analysis of the included studies, patients with COVID-19 had significantly low T/LH, FSH/LH, and SHBG levels and high levels of LH, and E2/T, but their levels of FT, FSH, PRL, E2, and progesterone were not affected. Publication bias was not found according to funnel plots and Egger’s regression and Begg’s rank correlation tests. Conclusion Low T/LH, FSH/LH, and SHBG serum levels and high LH, and E2/T levels may increase the risk of COVID-19. Additionally, the greater is the clinical severity of COVID-19, the higher is the probability of increases in LH, and E2/T serum levels and decreases in T/LH, FSH/LH, and SHBG levels. COVID-19 may have unfavourable effects on gonadal functions, which should be taken seriously by clinicians. Routine monitoring of sex hormone levels might help clinicians to evaluate disease severity in patients with COVID-19.